1988
DOI: 10.1021/bi00408a035
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence of guinea pig liver transglutaminase from its cDNA sequence

Abstract: Transglutaminases (EC 2.3.2.13) catalyze the formation of epsilon-(gamma-glutamyl)lysine cross-links and the substitution of a variety of primary amines for the gamma-carboxamide groups of protein-bound glutaminyl residues. These enzymes are involved in many biological phenomena. In this paper, the complete amino acid sequence of guinea pig liver transglutaminase, a typical tissue-type nonzymogenic transglutaminase, was predicted by the cloning and sequence analysis of DNA complementary to its mRNA. The cDNA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
103
1
2

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(116 citation statements)
references
References 49 publications
10
103
1
2
Order By: Relevance
“…We revealed that processing of TGase 1 is very specific, but by unknown protease(s) giving 20 times higher activity than intact form (Kim et al, 1995;. TGase 2 is an ubiquitous enzyme expressed in every cells and tissues (Ikura et al, 1988;Gentile et al, 1991). In the human epidermis, TGase 2 is expressed mostly in the supra basal layer and dermal layer which suggests it might be related with cell proliferation and extracellular matrix formation (Aeschilimann and Paulsson, 1991).…”
Section: Introductionmentioning
confidence: 83%
“…We revealed that processing of TGase 1 is very specific, but by unknown protease(s) giving 20 times higher activity than intact form (Kim et al, 1995;. TGase 2 is an ubiquitous enzyme expressed in every cells and tissues (Ikura et al, 1988;Gentile et al, 1991). In the human epidermis, TGase 2 is expressed mostly in the supra basal layer and dermal layer which suggests it might be related with cell proliferation and extracellular matrix formation (Aeschilimann and Paulsson, 1991).…”
Section: Introductionmentioning
confidence: 83%
“…In the region marked c in Fig. 4 2), which contains the transglutaminase active site in XIIIa (24) and LTG (25). The catalytic cysteine of the active sites of the transglutaminases and the corresponding alanine in P4.2 (see arrow in large box in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…4, b) (24,26,27) and LTG (25), especially around their active sites. XIIIa, the final component in the coagulation pathway, plays an important role in the stabilization of fibrin clots by covalently crosslinking fibrin monomers through y-glutamyl-E-lysine bridges and by preventing proteolysis (35).…”
Section: Methodsmentioning
confidence: 99%
“…These enzymes catalyze protein crosslinking reactions via the formation of e-(c-glutamyl)lysine bonds between the c-carboxyl group of a Gln residue in one polypeptide chain and the e-amino group of a Lys residue in a second polypeptide chain. Well-documented examples of TG are plasma factor XIIIa [2], keratinocyte TG [3], epidermal TG [4], tissue TG [5], and prostatic TG [6]. Recent findings have shown that, apart from their protein modifying capabilities, tissue TG is also able to function as a component of the signal-transducing G protein complex [7].…”
mentioning
confidence: 99%